2008
DOI: 10.1007/s10461-008-9456-3
|View full text |Cite
|
Sign up to set email alerts
|

Provider-related Barriers to Rapid HIV Testing in U.S. Urban Non-profit Community Clinics, Community-based Organizations (CBOs) and Hospitals

Abstract: We examined provider-reported barriers to rapid HIV testing in U.S. urban non-profit community clinics, community-based organizations (CBOs), and hospitals. 12 primary metropolitan statistical areas (PMSAs; three per region) were sampled randomly, with sampling weights proportional to AIDS case reports. Across PMSAs, all 671 hospitals and a random sample of 738 clinics/CBOs were telephoned for a survey on rapid HIV test availability. Of the 671 hospitals, 172 hospitals were randomly selected for barriers quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
2
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 41 publications
(40 reference statements)
0
26
2
1
Order By: Relevance
“…10-13,17 However, characteristics that distinguished programs offering testing from those who do not in national studies differed in some respects in our study. For example, unlike reports from other studies, testing in Arkansas was not provided by programs offering opiate substitution, medical detoxification, or programs with licensed medical staff.…”
Section: Discussioncontrasting
confidence: 60%
“…10-13,17 However, characteristics that distinguished programs offering testing from those who do not in national studies differed in some respects in our study. For example, unlike reports from other studies, testing in Arkansas was not provided by programs offering opiate substitution, medical detoxification, or programs with licensed medical staff.…”
Section: Discussioncontrasting
confidence: 60%
“…It is equally important that nontested participants mentioned relying often on physician recommendations, which, given medical provider discomfort with sexuality discussions with patients in general [70][71][72][73] and time constraint factors, 74 has implications for future programs that focus on increasing comfort with sexuality discussions in medical institutions targeting both providers and patients alike. 75,76 Peer norms, familial contexts, social support, and provider education should be integrated within STTR initiatives when considering programs that encourage HIV testing among Black men. 77 Our analysis of themes within the Health Behavior domain (i.e., personal health practices, use of health services) revealed that both tested and nontested participants often described seeking general health care, HIV tests, and STI tests in different locations (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study about the barriers to adoption of rapid HIV testing found that while 50% of hospital clinics had rapid HIV testing available, only 15% of respondents from clinics and community-based organizations did. 25 In our study focused on primary care settings, rapid testing appeared to be offered more commonly in community health centers and public hospital-based clinics, in settings with a higher prevalence of minority and uninsured patients, and in the northeastern US.…”
Section: Discussionmentioning
confidence: 99%